Exploring the structural validity and reliability of the swimming competence assessment scale in college students - Zhao, Miao; Chen, Cheng; Ning, Peng; Zhang, Bo Wei; Shen, Yupeng (Frontiers in Public Health, 2024)
PurposeAs a globally popular physical activity, swimming also presents challenges due to its inherent aquatic risks. Therefore, the cultivation of swimming competence emerges as a crucial strategy in preventing drowning incidents. This study aimed to develop and validate the Swimming Competence Assessment Scale in College Students (SCAS) to address the gap in structured swimming proficiency evaluation, essential for drowning prevention and water safety education.MethodsThe research involved 160 full-time second-year college students, including 92 males (age:20.48±0.51) and 68 females (age:20.65±0.70), who underwent two swimming ability assessments. The evaluation covered fundamental swimming skills, including entry, submersion, rotation, prone and supine swimming, floating, and exiting the water.ResultsExploratory Factor Analysis revealed goodness-of-fit for a two-factor model swimming coherent motion and swimming stable posture, which supported the construct validity. The inter-factor construct reliability (CR = 0.866, CR = 0.835) and the square root of Average Variance Extracted (AVE1 = 0.754, AVE1 = 0.848) exceeded the standards for supporting convergent and discriminant validity. The inter-rater reliability (IRR = 0.542) and Cronbach’s alpha (α = 0.840, α = 0.827) coefficient results have demonstrated the internal reliability of the SACS. Positive correlation between SCAS scores at pre-test and post-test provided evidence for SCAS’s test–retest reliability (TRR = 0.825, TRR = 0.758).ConclusionSCAS is a valid and reliable assessment scale. It assesses college students’ swimming competence through two aspects: Swimming Coherent Motion and Swimming Stable Posture.